Zakat and Waqf Managament in Indonesia and Pakistan: A Comparative Study - Marenza, Silvya Eka; Karimuddin, Karimuddin (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2024)
Zakat and waqf should be managed well so that they benefit society. This comparative study aims to analyse and compare the management practices of zakat and waqf in Indonesia and Pakistan. This study employs descriptive-comparative approach by analysing relevant literature, policies, and institutional frameworks in the management of zakat and waqf between Indonesia and Pakistan. Findings of this study reveal that both countries focus on strengthening transparency and accountability in the collection, distribution, and utilization of zakat and waqf funds. Nevertheless, there is a need for increased collaboration and coordination between government institutions, non-governmental organizations, and other stakeholders involved in zakat and waqf management in Indonesia and Pakistan. This study is significant because it has the potential to inform policies and strategies that can maximise the positive impact of zakat and waqf funds, resulting in more inclusive and equitable societies in both countries.